The Impact of Nurses' Fear of Covid-19 on Work Stress, Intention to Leave and Job Satisfaction with the Moderating Role of Supervisor Support - Fety Landari; Salamah Wahyuni (Nusantara Science and Technology Proceedings, 2022)
The Covid-19 pandemic is an unprecedented test for the healthcare system. They experience great pressure while treating patients infected with Covid-19, which will affect the quality of health services for patients. This study aims to assess the impact of nurses' fear of Covid-19 on work stress, intention to leave the organization and profession, and job satisfaction, moderated by supervisor support. The study was conducted with a cross-sectional approach and using a simple random sampling method in taking a sample of 222 nurses. Method of data analysis using multiple linear regression test. The results showed that the variable fear of Covid-19 affected work stress, intention to leave the organization and profession, and job satisfaction. The supervisor support variable as a moderator affected the relationship between the fear of Covid-19 variable with job stress and job satisfaction but did not affect the relationship between fear of Covid-19 and the intention to leave the organization and profession.